La proporcionalidad de la sanción en el tipo penal de secuestro extorsivo con violencia sexual - Sánchez Fernández, Chantal Dayana (2024)
ABSTRACT: This research named as “The proportionality of the sanction in the criminal offense of kidnapping for ransom with sexual violence” addresses the violation of the principle of criminal proportionality in the sanctioning of the crime of kidnapping for ransom with sexual violence. This multifaceted crime carries a maximum prison sentence of thirteen years, which is found to be proportionally less severe than the crime of rape. The main objective of this study is to conduct a legal analysis of the proportionality of the sanction in the criminal offense of kidnapping for ransom with sexual violence. This aims to assess the relevance of a partial reform project for the criminal types outlined in articles 162 and 171 of the Organic Integral Penal Code. The methodology employed for this research project involves a qualitative approach, utilizing deductive, descriptive legal, and exegetical methods. Moreover, this includes a dogmatic and descriptive legal research approach with a non-experimental design. The data collection process contains interviews with expert judges in the field, which has showed a violation of the principle of proportionality. The penalties imposed are found to be inadequate in relation to the severity of the crime committed. As a result, the proposed partial reform project is deemed pertinent. It suggests the repeal of numeral 10 of article 162 and its incorporation as a constitutive aggravating circumstance of the criminal offense of rape. This research sheds light on the importance of considering proportionality in criminal sanctions, particularly in cases involving kidnapping for ransom with sexual violence.